Study of macroscopic quantum tunnel junctions at high voltages and magnetic fields (2023)
This thesis describes the optimal fabrication processes to obtain large area and high-quality tunnel junctions with structure Al/Al2O3/Al(Metal/Insulator/Metal) and Al/Co/CoO/Al2O3/Al (Metal/Ferromagnet/Antiferromagnet/Insulator/Metal) grown on oxidized substrates of Si(100). It is found, these high-quality tunnel junctions can withstand large tunneling currents without suffering considerable damage. However, due to the difficulty of fabrication and the device's durability, a characterization method based on voltage pulses, that reduces dissipated power, is proposed to investigate the lifetime of tunnel junctions. Furthermore, it was possible to study the quantum tunneling effect at voltages close to the potential barrier height. At this voltage range, we show that the Simmons Model, the most widely used model to find the physical parameters of the potential barrier, is no longer accurate. We suggest a correction that includes energy dissipation during quantum tunneling processes that permits a more accurate data fitting at high voltages. Experiments also show the characteristic barrier height temperature dependence; where a reduction of around 1% is found as the temperature increases up to room temperature. Additionally, the dissipative model allowed the study of the dissipated energy in the junction as a function of the physical parameters of the barrier, the temperature, and the applied voltage. This analysis can be used to identify the relevant physical characteristics of the barrier for the tunnel junction to withstand larger currents reducing energy dissipation. Finally, in the search for greater control of the physical parameters of the potential barrier, a tunnel junction with a magnetic tunnel barrier was fabricated. With this experiment, we have found an apparent increase in barrier height of about 10% as the applied magnetic field increases. This percentual change is one order of magnitude greater than the characteristic increase found in barrier height due to temperature. Additionally, thanks to the magnetic response of the ferromagnet and antiferromagnet layers, it is possible to have asymmetric behavior for the tunneling currents. The polarity of the injected current determines different tunneling currents correlated with a variation of the physical parameters of the junction. This experimental evidence suggests magnetic barrier junctions deserve further study.